Metabolic anomalies in vitiligo: a new frontier for drug repurposing strategies - Paganelli, Alessia; Papaccio, Federica; Picardo, Mauro; Bellei, Barbara (Frontiers in Pharmacology, 2025)
Vitiligo is a chronic autoimmune condition characterized by the destruction of melanocytes, leading to patchy loss of skin depigmentation. Although its precise cause remains unclear, recent evidence suggests that metabolic disturbances, particularly oxidative stress and mitochondrial dysfunction, may play a significant role in the pathogenesis of the disease. Oxidative stress is thought to damage melanocytes and trigger inflammatory responses, culminating in melanocyte immune-mediate destruction. Additionally, patients with vitiligo often exhibit extra-cutaneous metabolic abnormalities such as abnormal glucose metabolism, dyslipidemia, high fasting plasma glucose levels, high blood pressure, out of range C-peptide and low biological antioxidant capacity, suggesting a potential link between metabolic impairment and vitiligo development. This implies that the loss of functional melanocytes mirrors a more general systemic targetable dysfunction. Notably, therapies targeting metabolic pathways, particularly those involving mitochondrial metabolism, such as the peroxisome proliferator-activated nuclear receptor γ (PPARγ) agonists, are currently being investigated as potential treatments for vitiligo. PPARγ activation restores mitochondrial membrane potential, mitochondrial DNA copy number and, consequently, ATP production. Moreover, PPARγ agonists counteract oxidative stress, reduce inflammation, inhibit apoptosis, and maintain fatty acid metabolism, in addition to the well-known capability to enhance insulin sensitivity. Additionally, increasing evidence of a strong relationship between metabolic alterations and vitiligo pathogenesis suggests a role for other approved anti-diabetic treatments, like metformin and fibrates, in vitiligo treatment. Taken together, these data support the use of approaches alternative to traditional immune-suppressive treatments for the treatment of vitiligo.